PENGARUH QUALITY OF WORK LIFE DAN KEPUASAN KERJA TERHADAP EMPLOYEE ENGAGEMENT PT. KERETA API INDONESIA (PERSERO) MEDAN - SAFIRA UTAMI (LP2MTBM MAKARIOZ, 2021)
This research study aims to study the effect of quality of work life and job satisfaction on employee engagement atPT. Kereta Api Indonesia (Persero) Medan. This type of research uses partially and simultaneously. The total population inthis study amounted to 95 people, and the samples were taken using the saturated sample method. And the analysistechnique used is multiple linear regression. The results showed that the quality of work life has a positive and significanteffect on employee engagement. Job satisfaction has a positive and significant effect on employee engagement. Quality ofwork life and job satisfaction have a positive and significant effect on employee engagement.